2019
DOI: 10.1177/1758573219866195
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of scapulothoracic fusion in facioscapulohumeral muscular dystrophy: A systematic review

Abstract: Background Facioscapulohumeral muscular dystrophy (FSHD) is a rare condition associated with selective weakness of the muscles of the upper arm, face, and shoulder girdle, negatively affecting daily activities. Scapulothoracic arthrodesis may restore shoulder function and improve quality of life. The purpose of this review is to evaluate the outcomes and complications of scapulothoracic arthrodesis in FSHD patients. Methods Medline, Pubmed, and Embase were systematically searched. Studies were included if they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…3,8,11 The union rate is seen to be higher with use of bone graft compared to without but iliac crest graft, which is often preferred, has a well-documented donor-site morbidity. 9,10,14 Scapulothoracic arthrodesis is known to have an overall pulmonary complication rate quoted at 46%, including iatrogenic lung injury from metalwork insertion, heamothoraces, pnuemothoraces, atelectasis and chest infections. 3 It is well-documented that occurrence of intercostal fusion (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,8,11 The union rate is seen to be higher with use of bone graft compared to without but iliac crest graft, which is often preferred, has a well-documented donor-site morbidity. 9,10,14 Scapulothoracic arthrodesis is known to have an overall pulmonary complication rate quoted at 46%, including iatrogenic lung injury from metalwork insertion, heamothoraces, pnuemothoraces, atelectasis and chest infections. 3 It is well-documented that occurrence of intercostal fusion (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…3 A recent systematic review of the literature reported that scapulothoracic fusion was associated with a decrease in pulmonary function, with reports of overall reduction in post-operative mean lung vital capacity, FVC and forced expiratory volume. [14][15][16][17][18] The technique of ST described in this report does not rely on metalwork used in the traditional plate-and-screw-fixation method necessary for arthrodesis. Hence, patients avoid issues of implant failure or hardware-related fractures, as well as associated complications and re-operation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study using EMG sensors fixed to the humerus and scapula, Harryman et al [12] demonstrated a high degree of functional motion in patients undergoing STF. This procedure was first described and is most commonly performed for scapulothoracic dysfunction in patients with muscular dystrophies such as facioscapulohumeral muscular dystrophy [5,7,8,14,15,18]. The procedure has been associated with improved cosmesis and overall function in patients with this rare condition.…”
Section: Introductionmentioning
confidence: 99%